2008
DOI: 10.1007/s00432-008-0358-6
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of methyl-aminolevulinate photodynamic therapy by iron chelation with CP94: an in vitro investigation and clinical dose-escalating safety study for the treatment of nodular basal cell carcinoma

Abstract: Purpose:Methyl-aminolevulinate (MAL) photodynamic therapy (PDT) is a cancer therapy that combines the selective accumulation of a photosensitizer in tumor tissue with visible light (and tissue oxygen) to produce reactive oxygen species. This results in cellular damage and ablation of tumor tissue. Combining iron chelators with MAL has the potential to increase the accumulation of the photosensitizer protoporphyrin IX (PpIX) by reducing its bioconversion to heme. This paper investigates this method of enhanceme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
2

Relationship

4
6

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 36 publications
(41 reference statements)
1
40
0
Order By: Relevance
“…S8). The lack of NHEK susceptibility to PpIX-based photodynamic cell killing under different conditions has previously been reported [40,41].…”
Section: Cells Cultured Long-term Under Hyperoxic Conditions Are Resimentioning
confidence: 72%
“…S8). The lack of NHEK susceptibility to PpIX-based photodynamic cell killing under different conditions has previously been reported [40,41].…”
Section: Cells Cultured Long-term Under Hyperoxic Conditions Are Resimentioning
confidence: 72%
“…[48,49]. Although these clinical investigations were only designed to assess safety, enhancements in tumour clearance were observed both clinically and histologically when CP94 was included within the photosensitising cream.…”
Section: Introductionmentioning
confidence: 99%
“…This finding indicated that greater PpIX accumulation increases the potential of the therapy as more PpIX is available for activation during irradiation. Therefore one of the main modalities of treatment enhancement focuses around increasing the level of PpIX within cells utilizing a variety of different techniques including lesion preparation (34), alternative prodrugs (35), penetration enhancers (36) and iron chelators (24,37).…”
Section: Introductionmentioning
confidence: 99%